TransTCR: Integrating TCRs and Transcriptomes Through Optimal Transport for Antigen Specificity Prediction - Wenbing Li; Yuansong Zeng; Ruipeng Huang; Yuanze Chen; Jinyun Niu; Ningyuan Shangguan; Siyuan He; Yuedong Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Inhalation and deposition characteristics of respiratory ultrafine and elongated mineral particles in the all-in-one human respiratory system: A CFD-based Study - Xueren Li; Qinyuan Sun; Jiang Li; Jiawei Ma; Ruipeng Xu; Jiaqi fan; Jie Li; Xinjian He; Xiang Fang; Yidan Shang; Jiyuan Tu (Journal of Hazardous Materials, 2026)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Developing Benzodithiophene-Free donor polymer for 19.36% efficiency Green-Solvent-Processable organic solar cells - Ying He; Wenwen Jing; Chentong Liao; Xiaopeng Xu; Yuwei Duan; Ruipeng Li; Liyang Yu; Qiang Peng (Chemical Engineering Journal, 2024)

A Manta Ray Robot with Soft Material Based Flapping Wing - Qimeng Liu; Hao Chen; Zhenhua Wang; Qu He; Linke Chen; Weikun Li; Ruipeng Li; Weicheng Cui (Journal of Marine Science and Engineering, 2022)
Recent research on robotic fish mainly focused on the bionic structure design and realizing the movement with smart materials. Although many robotic fish have been proposed, most of these works were oriented toward shallow water environments and are mostly built with purely rigid structures, limiting the mobility and practical usability of robotic fish. Inspired by the stability of the real manta ray, a manta ray robot design is proposed with soft material made flapping wing based on an open-source ROV (Remotely Operated Vehicle). The flapping wing structure with three different materials mimics the wide pectoral fins of real manta rays, which have bones, muscles, and skin. Furthermore, its modular design makes it easy to install and disassemble. The kinematic and hydrodynamic analysis of the manta ray robot are simulated in this paper. The actual manta ray robot is fabricated and several sets of test are performed in the pool. The robot can swim forward continually and stably with a simple rolling and pitching pattern.

Trophic Interaction in a Portunus rituberculatus Polyculture Ecosystem Based on Carbon and Nitrogen Stable Isotope Analysis - Jie Feng; Xiangli Tian; Shuanglin Dong; Da Li; Ruipeng He; Kai Zhang; Dongxu Zhang; Qingqi Zhang (Journal of Ocean University of China, 2018)